1918
DOI: 10.5962/bhl.title.134755
|View full text |Cite
|
Sign up to set email alerts
|

Determination of wilting ...

Abstract: The status of the question of permanent wilting in plants, as described by Briggs and Shantz (5, 6, 7, 8), Caldwell (ii), Shive and Livingston (37), and Alway (i), centers about the determination made by Briggs and Shantz that a plant is regarded as having attained a condition of permanent wilting when it does not recover its turgidity in a period of 24 hours when surrounded by air saturated with water vapor. The method of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

1921
1921
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…At this point, further, the curve of relative transpiration was found to show a marked and sudden rise which was independent of aerial conditions. Bakke (1,2) has shown that such a rise occurs at the wilting point of Helianthus. When Salix pentandra wilted under more extreme conditions in August the water content at that point was found to be 10-2 per cent.…”
Section: Methodsmentioning
confidence: 99%
“…At this point, further, the curve of relative transpiration was found to show a marked and sudden rise which was independent of aerial conditions. Bakke (1,2) has shown that such a rise occurs at the wilting point of Helianthus. When Salix pentandra wilted under more extreme conditions in August the water content at that point was found to be 10-2 per cent.…”
Section: Methodsmentioning
confidence: 99%
“…Veľkú pozornosť venuje tomu, ako boli v učebniciach vnímané české a slovenské vzťahy, a ako sa to do nich premietlo. Ďalšie práce, ktoré skúmajú formovanie kolektívnej identity v učebniciach dejepisu sú výskumy E. Bakke (1998, 1999) a P. Matulu (2013. Nórska autorka, E. Bakke, v jednej z kapitol svojej dizertačnej práce a následne vo svojej štúdii, analyzuje české a slovenské učebnice z rokov 1918 -1938 so zreteľom na pojmy identity, ktoré sprostredkovávajú -českú, slovenskú alebo československú.…”
unclassified